LAW ENFORCEMENT AGAINST CORRUPTION ERADICATION COMMISSION BASED ON LAW NO 19/2019 - Abdullah Abdullah; Otom Mustomi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Efforts to eradicate corruption have been carried out for a long time using various methods, sanctions against perpetrators of corruption have been intensified, but almost every day we still read or hear news about corruption. The dangers of corruption in Indonesia are equated with other extraordinary crimes, namely terrorism, drug abuse, or serious environmental damage. In fact, corruption with this status is on a par with extraordinary crimes based on the Rome Statute, namely crimes of genocide, crimes against humanity, and crimes of aggression. This study aims to analyze the role of the Corruption Eradication Commission in law enforcement against Corruption Crimes in Indonesia Based on Law no. 19 of 2019 concerning the Corruption Eradication Commission and efforts to overcome the occurrence of corruption in Indonesia. This study uses a normative juridical method, namely by referring to legal norms contained in laws and regulations and court decisions as well as legal norms that exist in society. The results of the study show that in seeking to eradicate corruption, there are several aspects that need to be addressed, namely the mentality and character of civil servants, policy makers, law enforcers and members of the public. In addition, law enforcers are required to implement a good control system and management system.